Analysis of the Influence of Service Access on the Utilization of Health Services at Community Health Centers - Miftahul Jannah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, Universitas Muhammadiyah Muara Bungo, 2024)
Health service accessibility regulations play a crucial role in determining the level of health service utilization in the community. Health centers provide health services to the community, while efforts to improve access to health services are important factors for quality health, including improving access to basic health services. The purpose of this study is to analyze the effect of service access on the utilization of health services in health centers. This study uses the method of Retrospective Observation, namely with a qualitative approach in Systematic Review to synthesize the research results. Literature searches are carried out online from Google Scholar and Publish and Perish using the keywords